PBL dengan pendekatan realistic mathematic meningkatkan nilai karakter siswa berkebutuhan khusus - Sandha Soemantri (Math Didactic: Jurnal Pendidikan Matematika, 2019)
In 2010, the government declared the nation's cultural and character education which was later linked to the condition of the Indonesian nation which showed anti-cultural and anti-character behavior. The development of character education is also felt by difabel students. The majority of students in PKBM Imanuel Surabaya are children of down syndrome and slow learners which results in them having difficulty socializing and understanding the study material. This study aims to improve the character values ​​and mathematical abilities of difabel students. Some principles in educating difabel students are the principle of group learning, the principles of skills, and the principle of adherence, so that the learning process in this study uses the Problem Based Learning (PBL) learning model through the Realistic Mathematic Education (RME) approach. This research is a classroom action research through the stages of Planning, Implementation, Observation, and Reflection. The results of the study after second cycle, the aspect of mathematical ability of all students reaches a value above the specified completeness standard, the average value of each character has reached a value of 3 and the average character value of each individual has also exceeded the value of 3.